セイケイ 90゜ カラ トウケイ 20゜ ニ イタル ナンキョク カイ オヨビ シュウヘン カイイキ ニ オケル エイヨウ エン ト クロロフィルa ノ ヒョウメン ブンプ - 福井, 深; フクイ, フカシ; 角谷, 伸之; カドヤ, ノブユキ; 岡部, 史郎; オカベ, シロウ; 小牧, 勇蔵; コマキ, ユウゾウ; Fukui, Fukashi; Kadoya, Nobuyuki; Okabe, Shiro; Komaki, Yuzo (1987)
P(論文) BIOMASS研究観測(SIBEX II)の一環として, 開洋丸による調査を1984年11-12月および1985年1月に実施し, 西経90度から東経20度に至る南極海および周辺海域の表面水の栄養塩およびクロロフィルaを測定した。栄養塩およびクロロフィルa平均濃度は亜熱帯海域から南極海へ南下するに従い増加した。南極海の地域的な濃度変化はリン酸塩と硝酸塩が少なく, ケイ酸塩は大きい。ケイ酸塩(71±7μM)の高い値がウェッデル海で得られ, また, Si : N : Pの原子比は44 : 16 : 1となった。これらの高いケイ酸塩は深層水の湧昇に起因していると推定された。 The surface distributions of chlorophyll a and nutrients were observed in the area between 90°W and 20°E of the Antarctic Ocean and adjacent seas in November and December 1984,and in January 1985,by R. V. KAIYO MARUas part of the national BIOMASS (SIBEX II) program. The mean concentrations of inorganic nutrients and chlorophyll a increase towared south from the Subtropical region to the Antarctic Ocean. Regional changes of phosphate and nitrate concentrations in the Antarctic water were small while those of silicate were large. High concentration of silicate (71±7μM) was found in the Weddell Sea, and the average atomic ratio of Si : N : P was 44 : 16 : 1. These high silicates may have resulted by upwelling from the deep water. departmental bulletin paper